Problematika Pengadaan Bilik Asmara di Lembaga Pemasyarakatan Kelas II A Parepare Demi Pemenuhan Hak Seksual Narapidana - Wiwin, Wiwin; Muhammad Sabir Rahman; Muhammad Aditya; Muhammad Kemal Yunus; Nurul Ramadhani Sangker (UNES Law Review, 2024)
A romance room is a special room or room provided by the state for inmates to channel their sexual desires. The provision of a romance room aims to provide a place for inmates to channel their sexual desires to their legal partners. In Indonesia, romance rooms are still limited and there are only three correctional institutions that have romance booths, namely Ciangir Class IIB Correctional Institution, Kendal Class IIB Open Correctional Institution, and Nusakambangan Class IIB Open Correctional Institution, while Parepare Class IIA Correctional Institution has not yet held a romance room. This study aims to find out the reality of inmates' sexual desire and the problems of procuring romance rooms in Class IIA Parepare Correctional Institution. This research is an empirical normative research that uses a statute appraoch, conceptual approach and social approach. The results of this study show that the reality of inmates' sexual desires in the Class IIA Parepare Correctional Institution requires a romance room as a legal mechanism to fulfill the inmates' sexual desires and to carry out the rights and obligations of the inmate's legal spouse in order to maintain marital harmony. Inmates of Class IIA Parepare Correctional Institution still have difficulty channeling their sexual desires because romance booths are not yet available, while CMK and extraordinary permits that are often used as a medium for channeling sexual desire require strict administrative requirements. The problems faced by the Parepare Class IIA Correctional Institution in the procurement of romance rooms are the absence of regulations that specifically regulate the requirements, implementation procedures, supervision, and technical matters related to the procurement of romance rooms. Another problem faced is the concern about the safety of the romance room and the impact caused if the inmate's wife or female inmate becomes pregnant and gives birth.